How Neuroimaging Can Aid the Interpretation of Art - Kesner, Ladislav; Adámek, Petr; Grygarová, Dominika (Frontiers in Human Neuroscience, 2021)
Cognitive neuroscience of art, continues to be criticized for failing to provide interesting results about art itself. In particular, results of brain imaging experiments have not yet been utilized in interpretation of particular works of art. Here we revisit a recent study in which we explored the neuronal and behavioral response to painted portraits with a direct versus an averted gaze. We then demonstrate how fMRI results can be related to the art historical interpretation of a specific painting. The evidentiary status of neuroimaging data is not different from any other extra-pictorial facts that art historians uncover in their research and relate to their account of the significance of a work of art. They are not explanatory in a strong sense, yet they provides supportive evidence for the art writer’s inference about the intended meaning of a given work. We thus argue that brain imaging can assume an important role in the interpretation of particular art works.